An economic evaluation of an augmented cognitive behavioural intervention vs. computerized cognitive training for post-stroke depressive symptoms. Issue 1 (December 2015) - van Eeden, M.; Kootker, J.; Evers, S.; Heugten, C.; Geurts, A.; van Mastrigt, G.
Abstract Background Stroke survivors encounter emotional problems in the chronic phase after stroke. Post-stroke depressive symptoms have major impact on health-related quality of life (HRQol) and lead to increased hospitalization and therefore substantial healthcare costs. We present a cost-effectiveness and cost-utility evaluation of a cognitive behavioural therapy augmented with occupational and movement therapy to support patients with a stroke with depressive symptoms in goal-setting and goal attainment (augmented CBT) in comparison with a computerized cognitive training program (CogniPlus) as a control intervention. Methods A trial-based economic evaluation was conducted from a societal perspective with a time horizon of 12 months. Stroke patients (aged 18+ years) with signs of depression (Hospital Anxiety and Depression Scale (HADS) – subscale depression > 7) were eligible to participate. Primary outcomes were the HADS and Quality Adjusted Life Years (QALYs) based on the three-level five-dimensional EuroQol (EQ-5D-3 L). Missing data were handled through mean imputation (costs) and multiple imputation (HADS and EuroQol), and costs were bootstrapped. Sensitivity analyses were performed to test robustness of baseline assumptions. Results Sixty-one patients were included. The average total societal costs were not significantly different between the control group (€9, 998.3) and the augmented CBT group (€8, 063.7), with a 95 % confidence interval (−5, 284, 1, 796). The augmented CBT intervention was less costly and less effective from a societal perspective on the HADS, and less costly and slightly more effective in QALYs, in comparison with the control treatment. The cost-effectiveness and cost-utility analyses provided greater effects and fewer costs for the augmented CBT group, and fewer effects and costs for the HADS. Based on a willingness to pay (WTP) level of €40, 000 per QALY, the augmented CBT intervention had a 76 % chance of being cost-effective. Sensitivity analyses showed robustness of results. Conclusion The stroke-specific augmented CBT intervention did not show convincing cost-effectiveness results. In addition to other literature, this study provided new insights into the potential cost-effectiveness of an adjusted cognitive behavioural therapy intervention. However, as our study showed a 76 % chance of being cost-effective for one outcome measure (QALY) and did not provide convincing cost-effectiveness results on the HADS we recommend further research in a larger population.